2015
DOI: 10.1038/nrrheum.2015.106
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis and targeted treatment of skin injury in SLE

Abstract: Skin is the second most common organ (after the kidney) to be affected in patients with systemic lupus erythematosus (SLE), yet the aetiology of skin injury and the mechanisms involved in the development of dermal manifestations of SLE remain unclear. Ultraviolet light (UV), immune cells, cytokines and deposition of immunoglobulins all seem to have a role in the development of skin inflammation and damage in SLE. UV represents the most important environmental factor, and exposure to UV triggers the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 105 publications
2
35
0
1
Order By: Relevance
“…IFN-κ is predominantly produced by human keratinocytes with pleiotropic effects similar to IFN-α/β (72). In SLE patients, keratinocytes have been implicated in the pathogenesis of skin injury by undergoing apoptosis or necrosis and eventually releasing autoantigens (73). Previous studies demonstrated that keratinocytes from patients with cutaneous lupus erythematosus presented increased production of IL-6 compared to healthy controls, with type I IFNs enhancing this process (74).…”
Section: Recent Findings On Systemic Sclerosis Reported the Abnormal mentioning
confidence: 99%
“…IFN-κ is predominantly produced by human keratinocytes with pleiotropic effects similar to IFN-α/β (72). In SLE patients, keratinocytes have been implicated in the pathogenesis of skin injury by undergoing apoptosis or necrosis and eventually releasing autoantigens (73). Previous studies demonstrated that keratinocytes from patients with cutaneous lupus erythematosus presented increased production of IL-6 compared to healthy controls, with type I IFNs enhancing this process (74).…”
Section: Recent Findings On Systemic Sclerosis Reported the Abnormal mentioning
confidence: 99%
“…Systemic lupus erythematosus (SLE) is a chronic autoimmune disease (AID) characterized by the destruction of immune regulation 1 , in which defects in Treg cell numbers and/or function have been observed both in patients and in a lupus-prone mouse model 26 . The mechanisms underlying the defects or deficiency of T regulatory (Treg) cells are variable, and include reduced capacity of suppression function, increased Treg cell apoptosis and the inhibition of Treg cell differentiation in the presence of high serum levels of proinflammatory cytokines such as interferon (IFN)-α, IFN-γ, interleukin (IL)-6, IL-1β and IL-17 79 .…”
Section: Introductionmentioning
confidence: 99%
“…Renal impairment is the most common and severe clinical manifestation of tissue damage seen in patients with SLE, and is characterized by immune complex deposition, inflammation, and scarring of glomeruli and interstitium; these are followed by skin injury, which also involves autoantibody production together with immune complex formation and deposition [137]. A source of autoantigens and endogenous molecules that promote inflammation is generated by apoptosis, a form of programmed cell death; nucleosomes containing nucleic acids with other endogenous ligands are incorporated in apoptotic blebs, a major source of such damaging molecules.…”
Section: Tissue Injury In Slementioning
confidence: 99%